Strategic environmental policy and the accumulation of knowledge - Thomas Ziesemer; Peter Michaelis (Universität Augsburg, Institut für Volkswirtschaftslehre, 2008)
Recent political discussions about the possible advantages of first-mover behaviour in terms of environmental policy again called attention to the well-established controversy about the effects of environmental regulation on international competitiveness. Conventional theory claims that the trade-off between regulation and competitiveness will be negative while the revisionist view, also known as the Porter Hypothesis, argues for the opposite. Several previous attempts that analysed this quarrel by means of strategic trade game settings indeed support the former claim and conclude that, to increase a firm's competitiveness, ecological dumping is the most likely outcome in a Cournot duopoly configuration. However, these results were derived from one period games in which so-called innovation offsets are unlikely to occur. The present paper considers a two-period model that includes an intertemporally growing firm-level knowledge capital. In doing so the accumulation of knowledge is modelled in a unilateral and a bilateral variant. It is shown that for both scenarios in period 1 the domestic government will set a higher emission tax rate compared to its foreign counterpart. Furthermore, we identify conditions for which the domestic tax rate will be set above the Pigouvian level in period 1 in both model variants.
urn:nbn:de:bvb:384-opus4-711320
Keywords: F18; Q55; Q58; 330; first-mover behaviour; Porter Hypothesis; strategic environmental policy; environ-mental regulation; international competitiveness